Quality of life among adults with hearing loss in Cantonal Hospital of Zenica: A cross-sectional study - Amel Krkalić; Admir Keserovic; Harun Selimović; Harun Mandra; Anes Jogunčić; Ragib Pugonja (Medicinski glasnik, 2025)
Aim: To assess Qualitiy of life (QoL) in adults by comparing two groups, the one with diagnosed hearing loss (HL) and the other without hearing complaints. Methods: This cross-sectional study included 110 consecutive voluntary adult patients divided in two groups: patients with hearing loss and control group. All participants , after examination , answered to a questionnaires on sociodemographic, clinical data and the World health Organization Quality of Life- Short version (WHOQOL-BREF). Results: Among 110 adults participants, 59 were with hearing loss (hearing loss group - HLG) and 19 in hearing loss with hearing aid group (HLHAG) and 51 in control group. Consistently higher score in the domains of physical health (p=0.036) and psychological health (p=0.024) in control group was found; other domains did not reach statistical significance Significant differences between the HLHAG and control group in physical health (mean difference = -11.3; p=0.036) and psychological health (mean difference = -11.3; p=0.029) was confirmed. Conculsion Hearing loss could decrease QoL. Therefore, it is very important to recognize hearing impairment in a timely manner and to take a serious approach to treatment.
Keywords: demographic factors; hearing aid; WHO QoL- bref